2011
DOI: 10.1074/jbc.m111.254235
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Extended Hydrogen Bond Network in the Binding Site of the Nicotinic Receptor

Abstract: The defining feature of the ␣ subunits of the family of nicotinic acetylcholine receptors is a vicinal disulfide between Cys-192 and Cys-193. Although this structure has played a pivotal role in a number of pioneering studies of nicotinic receptors, its functional role in native receptors remains uncertain. Using mutant cycle analysis and unnatural residue mutagenesis, including backbone mutagenesis of the peptide bond of the vicinal disulfide, we have established the presence of a network of hydrogen bonds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…We also found that Ala mutation of either of the closely located vicinal disulphides (C186, C187) decreased the affinity for epibatidine by > 30-fold. This is consistent with the increased EC 50 of ACh that is seen when the equivalent residue is mutated in other nACh receptor subtypes such as α1 subunit-containing nACh receptors (Blum et al., 2011, Karlin and Bartels, 1966). In α1 nicotinic subunits the disulphide bond formed by these adjacent Cys is proposed to distort loop C and enable key residues to interact with loop F on the opposite side of the binding interface, and at α7 nACh receptors they may have a similar role (Blum et al., 2011).…”
Section: Resultssupporting
confidence: 83%
“…We also found that Ala mutation of either of the closely located vicinal disulphides (C186, C187) decreased the affinity for epibatidine by > 30-fold. This is consistent with the increased EC 50 of ACh that is seen when the equivalent residue is mutated in other nACh receptor subtypes such as α1 subunit-containing nACh receptors (Blum et al., 2011, Karlin and Bartels, 1966). In α1 nicotinic subunits the disulphide bond formed by these adjacent Cys is proposed to distort loop C and enable key residues to interact with loop F on the opposite side of the binding interface, and at α7 nACh receptors they may have a similar role (Blum et al., 2011).…”
Section: Resultssupporting
confidence: 83%
“…Disulfide bonding on the surface of the human organic cation transporter 2 and the Cys-loop ligand-gated ion channel receptors was shown to have critical functional roles (20,21). Our functional assay showed that presence or absence of the two disulfide bonds in EL-3 had no demonstrable effect on NBCe1-A base transport, indicating that in the heterologous expression system the two disulfide bonds in EL-3 do not affect the baseline NBCe1-A base transport activity.…”
Section: Discussionmentioning
confidence: 75%
“…In the human organic cation transporter 2, cysteines in the extracellular loops play a crucial role in protein plasma membrane trafficking and are involved in transporter oligomerization (20). Moreover, in Cys-loop ligand-gated ion channel receptors, the disulfide bonds in a large extracellular loop are involved in forming the substrate interaction site (21). The TM prior to NBCe1-A EL-3 (TM5) contains a charged peptide motif 558 KKMIK 562 that forms one of the DIDS (an NBCe1-A functional inhibitor) binding sites (22).…”
Section: ϫmentioning
confidence: 99%
“…As shown in Figure 4, the SS and its Loop C moves the farthest (about 10Å) in the allosteric conformational change underlying channel activation 39, 45 . Thermodynamic cycles for mutations which include modifying the vicinal SS peptide backbone 46 have recently shown that involvement of a cis/trans conversion in receptor function is highly unlikely, but have strongly implicated an intersubunit H-bond network between the vicinal SS NH and an Asp on the complementary face as critical to nAChR ion-channel function.…”
Section: Resultsmentioning
confidence: 99%